First international comparison of fountain primary frequency standards via a long distance optical fiber link. (8th May 2017) - Guéna, J; Weyers, S; Abgrall, M; Grebing, C; Gerginov, V; Rosenbusch, P; Bize, S; Lipphardt, B; Denker, H; Quintin, N; Raupach, S M F; Nicolodi, D; et al.
Abstract: We report on the first comparison of distant caesium fountain primary frequency standards (PFSs) via an optical fiber link. The 1415 km long optical link connects two PFSs at LNE-SYRTE (Laboratoire National de métrologie et d'Essais—SYstème de Références Temps-Espace) in Paris (France) with two at PTB (Physikalisch-Technische Bundesanstalt) in Braunschweig (Germany). For a long time, these PFSs have been major contributors to accuracy of the International Atomic Time (TAI), with stated accuracies of around 3 × 10 − 16 . They have also been the references for a number of absolute measurements of clock transition frequencies in various optical frequency standards in view of a future redefinition of the second. The phase coherent optical frequency transfer via a stabilized telecom fiber link enables far better resolution than any other means of frequency transfer based on satellite links. The agreement for each pair of distant fountains compared is well within the combined uncertainty of a few 10 −16 for all the comparisons, which fully supports the stated PFSs' uncertainties. The comparison also includes a rubidium fountain frequency standard participating in the steering of TAI and enables a new absolute determination of the 87 Rb ground state hyperfine transition frequency with an uncertainty of 3.1 × 10 − 16 . This paper is dedicated to the memory of André Clairon, who passed away on 24 December 2015, for his pioneering and long-lasting efforts in atomic fountains. He also pioneered optical links from as early as 1997.